CAPITAL EXPENDITURE DAN OPERATIONAL EXPENDITURE DALAM PERANCANGAN INSTALASI PENGOLAHAN AIR DI KOTA BALIKPAPAN - Widya Mulya (Universitas Lambung Mangkurat, 2022)
The study of project financial feasibility data is prepared based on the theory of project financial management which is inventoried and processed based on the parameter requirements and financial feasibility criteria such as the initial investment budget/capital expenditure (CAPEX) and operational expenditure operating budget (OPEX). Lack of planning and consultation (in relation to project planning) causes high project costs (project costs) and the realization of infrastructure development that is past its deadline (program over-runs) (Asian Development Bank, 2021). Economic analysis determines that the decision to invest in a project is correct from the point of view of economic benefits. Balancing the effects of investing in a project as an advantage, not only for the project management itself, but for the entire community. The water treatment plant is one of the infrastructures that treats raw water (ground water, surface water) into water suitable for consumption in accordance with quality standards. The larger the initial investment budget and the operational cost budget, the higher the cost of treated water. The purpose of this research is to determine the cost of treated water from the calculation of capital expenditure and operational expenditure in the design of water treatment installations in Balikpapan City. CAPEX budget calculations are based on engineering costs, land acquisition costs and construction costs. The OPEX budget includes operating costs, maintenance costs, depreciation expense, administrative and general expenses. Based on the analysis of raw water sources and treatment types, the cost of treated water for conventional treatment types is Rp. 6,197/m³, the cost of DAF type treated water is Rp. 6,991/m³, the cost of RO treated water is Rp. 14,298/m³.